Work-Life Balance, Organizational Commitment, and Job Performance: The Moderating Role of Job Satisfaction - Agustina (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the determinants of nurse performance in Kendari City by examining the influence of Work Life Balance and job satisfaction and evaluating the role of organizational commitment as a mediating variable and job satisfaction as a moderator. Using an explanatory quantitative approach with Structural Equation Modeling analysis techniques based on Partial Least Squares or SEM PLS, this study involved 160 nurses as respondents who were selected through a structured survey method. The results of statistical analysis provide empirical evidence that Work Life Balance has a positive and significant impact on performance and is a very strong predictor for the formation of organizational commitment. In contrast, partial job satisfaction was shown to have no significant direct effect on performance, but important findings from the interaction test suggest that this variable functions effectively as a moderator that strengthens the relationship between organizational commitment and performance. This indicates that new job satisfaction will have a real impact on improving work outcomes if synergized with high organizational loyalty so that work-life balance and commitment are vital keys in optimizing health services in this region.